2004
DOI: 10.1001/archotol.130.5.499
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model for Cochlear Implants

Abstract: To test the feasibility of using the deaf white cat model of early-onset deafness. We studied the neuronal effects of prosthetic intervention with a clinical, "offthe-shelf" multichannel cochlear implant. Methods: We placed cochlear implants in 5 deaf white kittens at age 12 and 24 weeks. The devices were activated and stimulated in the laboratory using a clinical speech processor programmed with a high-resolution continuous interleaved sampling (CIS) strategy for 8 to 24 weeks. Stimulus parameters were guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The positive peaks of the EABRs in the cat experience were similar to those reported in a study by Kretzmer et al [16] in which Clarion II high-focus implants from the Advanced Bionics Corporation CI that were manufactured with smaller 6-electrode arrays for use in cats were examined. The waveforms of the EABR revealed that the Nurotron Õ Venus TM Cochlear Implant System was able to effectively stimulate the feline auditory system.…”
Section: Discussionsupporting
confidence: 82%
“…The positive peaks of the EABRs in the cat experience were similar to those reported in a study by Kretzmer et al [16] in which Clarion II high-focus implants from the Advanced Bionics Corporation CI that were manufactured with smaller 6-electrode arrays for use in cats were examined. The waveforms of the EABR revealed that the Nurotron Õ Venus TM Cochlear Implant System was able to effectively stimulate the feline auditory system.…”
Section: Discussionsupporting
confidence: 82%
“…Previously published feline implantation techniques were used (2,6,7). Approval was obtained from both the Georgia Regents University, and the Georgia Institute of Technology Institutional Animal Care and Use Committees.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical approach was modeled after previously published feline studies by Rajguru et al, (2) Kretzmer et al, (6) and Kirby and Middlebrooks (7). One of 2 surgeons performed each insertion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three normal-hearing cats (one white and two pigmented), seven congenitally deaf white cats, and eight congenitally deaf white cats with unilateral cochlear implants were used. The implanted cats have contributed unrelated data to other studies (Kretzmer et al 2004;Ryugo et al 2005;O'Neil et al 2010). Spiral ganglion cell counts were also used from cats whose numbers were previously published by others (n=4, Howe 1934;n=1, Gacek and Rasmussen 1961;n=54, Mair 1973).…”
Section: Experimental Groupsmentioning
confidence: 99%